2017
DOI: 10.1364/oe.25.022620
|View full text |Cite
|
Sign up to set email alerts
|

11-fs dark pulses generated via coherent absorption in plasmonic metamaterial

Abstract: Abstract:We demonstrate generation of the shortest reported 11fs dark pulses using the coherent absorption process on a plasmonic absorber with a gating pulse. The dark pulses appear as a power dip on the envelope of a long carrier pulse and are characterized using the cross-correlation technique. The principal difference and advantage of our approach in comparison with previously developed laser sources of dark pulses is that, in principle, it allows transferring arbitrary pattern of bright pulses into a patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…While our experimental equipment does not allow us to test the performance of the modulator in the fibre environment beyond 40 Gbit/s, we expect that the metadevice can in principle operate at much higher frequencies. Indeed, the underlying phenomena of coherent absorption and coherent transparency in plasmonic metamaterials occur on timescales as short as 10 fs implying a potential bandwidth on the order of 100 THz [10]. Comparison of the absorption characteristics of such an ultrafast coherent absorber to those of our metadevice indicates that the metamaterial used in our metadevice may be expected to efficiently absorb pulses as short as 40 fs, corresponding to a potential bandwidth of 10s of THz for our device, see Supplementary Information.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…While our experimental equipment does not allow us to test the performance of the modulator in the fibre environment beyond 40 Gbit/s, we expect that the metadevice can in principle operate at much higher frequencies. Indeed, the underlying phenomena of coherent absorption and coherent transparency in plasmonic metamaterials occur on timescales as short as 10 fs implying a potential bandwidth on the order of 100 THz [10]. Comparison of the absorption characteristics of such an ultrafast coherent absorber to those of our metadevice indicates that the metamaterial used in our metadevice may be expected to efficiently absorb pulses as short as 40 fs, corresponding to a potential bandwidth of 10s of THz for our device, see Supplementary Information.…”
Section: Resultsmentioning
confidence: 91%
“…However, recently it was shown that an effective nonlinear response may be derived from coherent interaction of light with light on linear materials of substantially subwavelength thickness [7]. In contrast to conventional optical nonlinearities, the effect has been shown to allow intensity-independent control over absorption of light, from almost 0% to almost 100% [8], with 100 THz bandwidth [9,10] and even for single photon signals [11]. The concept has enabled all-optical control of luminescence * Electronic address: ax1c15@soton.ac.uk † Electronic address: erp@orc.soton.ac.uk ‡ Electronic address: niz@orc.soton.ac.uk; URL: www.…”
mentioning
confidence: 99%
“…In contrast, all-optical processing of mutually coherent signals does not require optical nonlinearity [9]. Similarly, nonlinear dark pulse generation [10][11][12][13][14][15][16][17][18][19] and nonlinear dark soliton propagation [10,[20][21][22][23] in optical fibres at high intensities are well-known, but the shortest dark pulses have been generated by linear methods in free space [21,24]. Recent developments in dark pulse generation and coherent all-optical signal processing exploit the fact that modulation of light with light may be derived from the interaction of mutually coherent optical signals in a linear material of substantially subwavelength thickness [25].…”
mentioning
confidence: 99%
“…Such all-optical modulation allows control over the absorption of light from "coherent perfect absorption" to "coherent perfect transmission" and is intensity-independent down to single photon signal levels [26]. It has enabled 11 fs dark pulse generation [24], polarization modulation, image processing and various logic functions in free space [25]. Recently, the concept was applied to demonstrate NOT, XOR and AND functions at up to 40 Gbit/s in a fibre-optic interferometer [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation